The CNG corpus of European Portuguese children's speech - Dias, José Miguel de Oliveira Monteiro Sales (2016)
Speech recognisers trained with adults' speech do not work well with children's speech because of the inherent acoustic and linguistic differences in the speech of these two populations. To develop speech-driven applications capable of successfully recognising children's speech, a sufficient amount of children's speech is needed for training acoustic models from scratch or for adapting acoustic models trained with adults' speech. However, the availability of suitable children's speech corpora is still limited, especially in the case of less-spoken languages. This paper describes the design, collection, transcription and annotation of a 21-hour corpus of prompted European Portuguese children's speech collected from 510 children aged 3-10. Before the development of this corpus, European Portuguese children's speech data have not been available at all for parts of this age range.